Fabricação de novos filamentos condutores para a produção de sensores eletroquímicos - Fernandes Junior, Wilson Silva (2025)
Additive manufacturing allows the production of objects layer upon layer from three-dimensional models, reducing costs and enabling mass production. Electrochemical sensors printed through additive manufacturing require conductive filaments, but commercial ones are expensive and imported, in addition to having inferior performance. Laboratory-produced filaments stand out by reducing import dependence and allowing for control over electrical conductivity. With electrochemical sensors made from these filaments, it is possible to detect various analytes, such as antibiotics. Sulfamethoxazole and sulfadiazine are antibiotics used to treat pathogenic bacterial infections in cattle and humans. However, when administered in high doses or improperly, these drugs can cause bioaccumulation in humans and animal-derived products. Therefore, the aim of this work was to manufacture a conductive filament using carbon black, multi-walled carbon nanotubes, and polylactic acid, used in the production of sensors to determine sulfamethoxazole and sulfadiazine in water and milk samples, in a linear range of 5.0 to 60 μmol L−1 and 5.0 to 50 μmol L−1, respectively, with a limit of detection of 0.3 μmol L−1 for both, demonstrating high efficiency for electrochemical applications.